Trends in Transcatheter and Surgical Aortic Valve Replacement Among Older Adults in the United States - Mori, Makoto; Gupta, Aakriti; Wang, Yun; Vahl, Torsten; Nazif, Tamim; Kirtane, Ajay J; George, Isaac; Yong, Celina M; Onuma, Oyere; Kodali, Susheel; Geirsson, Arnar; Leon, Martin B; et al. (Journal of the American College of Cardiology, 2021)
Recent trends, including survival beyond 30 days, in aortic valve replacement (AVR) following the expansion of indications for transcatheter aortic valve replacement (TAVR) are not well-understood. The authors sought to characterize the trends in characteristics and outcomes of patients undergoing AVR. The authors analyzed Medicare beneficiaries who underwent TAVR and SAVR in 2012 to 2019. They evaluated case volume, demographics, comorbidities, 1-year mortality, and discharge disposition. Cox proportional hazard models were used to assess the annual change in outcomes. Per 100,000 beneficiary-years, AVR increased from 107 to 156, TAVR increased from 19 to 101, whereas SAVR declined from 88 to 54. The median [interquartile range] age remained similar from 77 [71-83] years to 78 [72-84] years for overall AVR, decreased from 84 [79-88] years to 81 [75-86] years for TAVR, and decreased from 76 [71-81] years to 72 [68-77] years for SAVR. For all AVR patients, the prevalence of comorbidities remained relatively stable. The 1-year mortality for all AVR decreased from 11.9% to 9.4%. Annual change in the adjusted odds of 1-year mortality was 0.93 (95% CI: 0.92-0.94) for TAVR and 0.98 (95% CI: 0.97-0.99) for SAVR, and 0.94 (95% CI: 0.93-0.95) for all AVR. Patients discharged to home after AVR increased from 24.2% to 54.7%, primarily driven by increasing home discharge after TAVR. The advent of TAVR has led to about a 60% increase in overall AVR in older adults. Improving outcomes in AVR as a whole following the advent of TAVR with increased access is a reassuring trend.